Influence of Gamification Media on the Learning Activities of Sociology in The High School of Surakarta - Ambawani, Cettra Shandilia Latunusa; Kusuma, Thitha Meista Mulya; Yunianto, Aan; Murtiyasa, Budi; Masduki, Masduki; Haryanto, Sigit (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2024)
Education influences students to be innovative, creative, and productive individuals. The study aims to find out the impact of gamification media use on educational activities in schools in Surakarta. Quantitative Research Methods with Survey Approaches to Higher Secondary Schools in Surakarta. Measurements in using SPSS 25 with Cronbach’s alpha variable learning media gamification and pupil activity, normality tests, heterocadastisity tests, deviations, correlation values, and determination coefficients (R square) The collection shows that H0 is rejected and Ha is accepted because the regression factor has a value of significance < 0.05, so some suggest that there is a significant influence between the use of gamified media and activation. The study results show that the correlations or relations values table (R) is 0.335 and a determination factor (R square) of 0.112 means that the influence of the gamifying media (X) on the activity (Y) is 11.2%, partially suggesting that there are significant influences between the usage of gamification media and student activity.